Impact Of Covid -19 Pandemic on Foreign Direct Investment in Nepal from South Asian Perspectives - Chaudhary, Manoj Kumar; Ghimire, Rudra Prasad; Ghimire, Dinesh Mani (Universitas Airlangga, 2020)
Foreign Direct Investment (FDI) is an essential source of economic development. It has a broad relationship with different dimensions of the mixed economies. Like other development assistance, FDI also needs the best economic environment. This investigation aims to find the impact of Covid -19 on FDI inflow and other barriers to receiving FDI commitment in Nepal. This study is descriptive and analytical. Secondary data are used in the study. Foreign direct investment can be obtained as the government prioritized agriculture, tourism, energy, IT, infrastructure, etc., considering rapid economic Development. The government of Nepal is accepting and implementing foreign investment proposals of donor commitments. However, the Covid -19 pandemic has reduced FDI commitments funds as envisioned. Pandemic is not the only barrier of investment commitment. Still, there are also investment barriers are like, Business environment, poor infrastructure, lack of human resource skills, political transitions, weak governance, natural calamities, diverse and complex geography, tax slab, red tape, and climate change are critical in Nepal. Though the FDI in Nepal till 2019 was an upward trajectory, the 2020 pandemic has reduced it as Nepal's primary economic development source. South Asian environment can create FDI friendly environment in Nepal. Finally, this paper is a new one and full authority for future researchers. Keywords: Covid-19 pandemic, Foreign Direct Investment, Commitment, Business Environment, Nepal JEL: F23, I1, M0